2019
DOI: 10.1186/s12870-018-1605-x
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical properties and subcellular localization of six members of the HXK family in maize and its metabolic contribution to embryo germination

Abstract: BackgroundSeed germination is a crucial process in the plant life cycle when a dramatic variation of type and sugar content occurs just as the seed is hydrated. The production of hexose 6 phosphate is a key node in different pathways that are required for a successful germination. Hexokinase (HXK) is the only plant enzyme that phosphorylates glucose (Glc), so it is key to fueling several metabolic pathways depending on their substrate specificity, metabolite regulatory responses and subcellular localization. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 71 publications
0
14
0
Order By: Relevance
“…Cluster 4 encompassed genes coding for mitochondrion and respiratory chain components, genes related to ribosomes and translation, Golgi apparatus, endoplasmic reticulum, and vesicle mediated transport. We also found genes encoding for key enzymes involved in fatty acid beta-oxidation and glyoxylate cycle (MLS, ICL, Comai et al, 2007), tricarboxylic acid cycle (ACO3, CSY3, Pracharoenwattana et al, 2005; Hooks et al, 2014), carbohydrate biosynthesis, and glycolysis (HXK1, Aguilera-Alvarado et al, 2019). In the case of BnaHKX1 , we found that the peaking time point in C033 and C032 was delayed compared to C129 ( Supplementary Figure S3 ).…”
Section: Resultsmentioning
confidence: 92%
“…Cluster 4 encompassed genes coding for mitochondrion and respiratory chain components, genes related to ribosomes and translation, Golgi apparatus, endoplasmic reticulum, and vesicle mediated transport. We also found genes encoding for key enzymes involved in fatty acid beta-oxidation and glyoxylate cycle (MLS, ICL, Comai et al, 2007), tricarboxylic acid cycle (ACO3, CSY3, Pracharoenwattana et al, 2005; Hooks et al, 2014), carbohydrate biosynthesis, and glycolysis (HXK1, Aguilera-Alvarado et al, 2019). In the case of BnaHKX1 , we found that the peaking time point in C033 and C032 was delayed compared to C129 ( Supplementary Figure S3 ).…”
Section: Resultsmentioning
confidence: 92%
“…It is known that mammal HXKI-III glucose phosphorylating activity are product-regulated: physiological concentrations of G6P can allosterically inhibit its activity in a non-competitive way with respect to glucose, but competitive to ATP ( Van Schaftingen, 2013 ). In maize, mitochondrial attached HXKs are less inhibited by G6P and ADP than the cytosolic HXKs ( Aguilera-Alvarado et al, 2019 ), suggesting that their subcellular localization is a key component to control its enzyme activity.…”
Section: Regulation Mechanisms Of Hexokinases’ Moonlighting Functionsmentioning
confidence: 99%
“…A distinct feature of some hexokinases that might contribute to its moonlighting activity is their subcellular location: some of them, like S. cerevisiae HXK2 ( Fernández-García et al, ) and maize HXK7 and HXK8 ( Aguilera-Alvarado et al, 2019 ) are located at the cytoplasm; others, in glycosomes, like T. brucei HXK2 ( Blattner et al, 1995 ; Michaels et al, 2006 ); many in the mitochondrial outer membrane or MOM, like human HXKII ( Arora and Pedersen, 1988 ; Dubey et al, 2016 ), A. thaliana HXK1 ( Cho et al, 2006a ) and apple HXK1 ( Sun et al, 2018 ); or in the chloroplast, like P. patens HXK1 ( Olsson et al, 2003 ) and Oryza sativa HXK4 ( Cho et al, 2006a ). And even there are HXKs that are translocated from one subcellular compartment to the nucleus, like AtHXK1 ( Cho et al, 2006b ) and ScHXK2 ( Vega et al, 2016 ).…”
Section: Regulation Mechanisms Of Hexokinases’ Moonlighting Functionsmentioning
confidence: 99%
“…Out of these, 18 genes ( GRMZM2G105571 , Zm00001d027469 , Zm00001d043622 , GRMZM2G353553 , GRMZM2G167856 , GRMZM2G171373 , GRMZM2G092120 , CKX10 , GRMZM2G035217 , GRMZM2G128644 , GRMZM2G314064 , GRMZM2G407825 , GRMZM6G865522 , GRMZM2G045732 , pco092737 , Zm00001d002111 , GRMZM2G042412 , and GRMZM2G061537 ) were associated with a minimum of two traits. In addition, some of them [ GRMZM2G105571 ( Li et al, 2018 ), GRMZM2G167856 ( Li et al, 2016 ), GRMZM2G171373 ( Aguilera-Alvarado et al, 2019 ), CKX10 ( Smehilova et al, 2009 ), GRMZM2G128644 ( Song et al, 2016 ), GRMZM2G314064 ( Jiang et al, 2012 ), GRMZM2G407825 ( Yan et al, 2017 ), etc.] had been reported by previous studies of maize seed and leaf, which was consistent with our study.…”
Section: Resultsmentioning
confidence: 99%